2014
DOI: 10.1371/journal.pone.0112089
|View full text |Cite
|
Sign up to set email alerts
|

A High-Density Genetic Map Identifies a Novel Major QTL for Boron Efficiency in Oilseed Rape (Brassica napus L.)

Abstract: Low boron (B) seriously limits the growth of oilseed rape (Brassica napus L.), a high B demand species that is sensitive to low B conditions. Significant genotypic variations in response to B deficiency have been observed among B. napus cultivars. To reveal the genetic basis for B efficiency in B. napus, quantitative trait loci (QTLs) for the plant growth traits, B uptake traits and the B efficiency coefficient (BEC) were analyzed using a doubled haploid (DH) population derived from a cross between a B-efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 49 publications
1
61
0
Order By: Relevance
“…Moreover, many traits of agronomic importance in B. napus , such as seed coat color, oil content, and seed yield, are quantitative with complex genetic bases. Recently, a high-density linkage map was constructed using the Brassica 60 K Infinium BeadChip Array (Zou et al, 2012; Delourme et al, 2013; Liu et al, 2013; Zhang et al, 2014; Wang et al, 2015). Genome-specific SSR markers have been widely used for genetic mapping, association mapping, comparative mapping, QTL analysis, and marker-assisted selection (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many traits of agronomic importance in B. napus , such as seed coat color, oil content, and seed yield, are quantitative with complex genetic bases. Recently, a high-density linkage map was constructed using the Brassica 60 K Infinium BeadChip Array (Zou et al, 2012; Delourme et al, 2013; Liu et al, 2013; Zhang et al, 2014; Wang et al, 2015). Genome-specific SSR markers have been widely used for genetic mapping, association mapping, comparative mapping, QTL analysis, and marker-assisted selection (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Many other candidate genes were identified that are associated with the variation of number of pods per plants. Among the candidate genes, basic helixloop-helix (bHLH) DNA-binding superfamily protein that is involved in the development and dehiscence of seed and pod (Hudson and Hudson, 2015), protein kinase superfamily protein is involved in pollen abortion (Radchuk et al, 2006), pyruvate kinase family protein associated with early embryo abortion of flower (Zhang et al, 2014), ARM repeat superfamily protein is involved in self-incompatibility and reduction of pod number (Sharma and Pandey, 2016), chaperone DNAJ-domain superfamily protein is involved in male sterility (Yang et al, 2009), DNAJ heat shock Nterminal domain-containing protein that increases tolerance to heat and prevents fruit drop (Zhao et al, 2015), prolinerich family protein associated with flower and pod development (Giorno et al, 2013), adenine nucleotide alpha hydrolases-like superfamily protein is involved in male sterility (Mok and Mok, 2001), homeodomain-like protein regulates anther dehiscence (Wilson et al, 2011), cytochrome P450 is involved in the pollen tube development and fertilization (Zhao et al, 2015), pyruvate kinase family protein found associated with early embryo abortion (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Pod length is also affected by heat stress. High temperature reduces the photosynthetic capacity (CraftsBrandner and Salvucci, 2002) and increase pollen abortion (Zhang et al, 2014), which in turn affects the growth and development of pod. We have identified 11 QTL associated with pod length in relation to heat stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve quality and yield in crops, molecular markers have been widely used to study germplasm diversity [4,5]. To date, numerous molecular marker technologies continue to be developed and used in plant genetic analysis.…”
mentioning
confidence: 99%